2020
DOI: 10.1177/0271678x20902542
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and functional studies reveal undermined chemotactic and angiostimulatory properties of aged microglia during stroke recovery

Abstract: Age-dependent alterations in microglia behavior have been implicated in neurodegeneration and CNS injuries. Here, we compared the transcriptional profiles of young versus aged microglia during stroke recovery. CD45intermediateCD11b+ microglia were FACS-isolated from the brains of young (10-week-old) and aged (18-month-old) male mice with sham operation or 14 days after distal middle cerebral artery occlusion and subjected to RNA-sequencing analysis. Functional groups enriched in young microglia are indicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…Changes of the immune response with a shift towards a proinflammatory state and alterations of microglial differentiation and function are thought to play a key role for the reduced regenerative capacity of older brains. 115 117 There is even evidence for changes in the gut microbiota of aged mice followed by increased levels of systemic proinflammatory cytokines resulting in worse outcome after stroke. 118 Not so surprisingly, there is proof that not only the endogenous regenerative capacity of the aged brain is reduced but also the response to various treatments when compared to younger animals.…”
Section: Specific Requirements and Pitfalls In Recovery Studiesmentioning
confidence: 99%
“…Changes of the immune response with a shift towards a proinflammatory state and alterations of microglial differentiation and function are thought to play a key role for the reduced regenerative capacity of older brains. 115 117 There is even evidence for changes in the gut microbiota of aged mice followed by increased levels of systemic proinflammatory cytokines resulting in worse outcome after stroke. 118 Not so surprisingly, there is proof that not only the endogenous regenerative capacity of the aged brain is reduced but also the response to various treatments when compared to younger animals.…”
Section: Specific Requirements and Pitfalls In Recovery Studiesmentioning
confidence: 99%
“…However, under pathological conditions, the effect of microglial phagocytosis is considered to be paradoxical 4 . On one hand, microglia phagocytosis may prevent secondary apoptosis‐induced inflammation by releasing anti‐inflammatory cytokines and by inhibiting pro‐inflammatory cytokines 5 . On the other hand, microglial phagocytosis appears to activate respiratory burst, resulting in the release of neurotoxic reactive oxygen species (ROS) 4 .…”
Section: Introduction and Classification Of Pathological Microglial Pmentioning
confidence: 99%
“…As resident microglia serve pro‐angiogenic effects in the brain (Brandenburg et al, 2016; Jiang et al, 2020; Mastorakos et al, 2021), we co‐stained Iba‐1 and isolectin B4 on brain sections of 9‐month‐old APP tg Myd88 fl/wt Cre +/− and APP tg Myd88 fl/wt Cre −/− mice and counted microglia with and without contact with blood vessels in CA1 area of the hippocampus (Figure 5f). We observed that haploinsufficiency of MyD88 significantly increased the distribution of microglia to blood vessels (Figure 5g; one‐way ANOVA followed by post‐hoc test, p <.05).…”
Section: Resultsmentioning
confidence: 99%